Tunable Class AB CMOS Gm-C Filter Based on Quasi-Floating Gate Techniques - Garcia-Alberdi, Coro; Lopez-Martin, Antonio J.; Acosta, Lucia; Carvajal, Ramon G.; Ramirez-Angulo, Jaime (IEEE transactions on circuits and systems. I, Regular papers, 2013)
A tunable CMOS Gm-C channel-select low-pass filter is presented. Class AB operation overcomes the dynamic range versus static power tradeoff of conventional channel-select filter topologies. Programmable transconductors are designed using quasi-floating gate transistors, which provide class AB operation without requiring extra supply voltage or power requirements and keeping accurately set quiescent currents. The filter can be applied to channel selection in highly integrated, low power zero-IF wireless receivers. For example, its frequency tuning range and linearity makes it suitable for a dual-mode Bluetooth/ZigBee zero-IF receiver. Measurement results for a test chip prototype in a 0.5 μm standard CMOS process are presented, showing a THD <; -55 dB for an input of 1.2 Vpp, which corresponds to peak currents 300% larger than the bias current.